d-Alanine Oxidase from Escherichia coli: Participation in the Oxidation of l-Alanine - Raunio, R. P. (1973)
Cell wall-membrane preparations of Escherichia coli, prepared by the ethylenediaminetetraacetic acid-lysozyme method, contain enzymes which catalyze the oxidation of d-alanine and, to a lesser extent, l-alanine into pyruvate and ammonia without the formation of hydrogen peroxide. The kinetic parameters were (i) pH optima of 8.3 to 8.4 for l- and d-alanine and (ii) a K(m) value of 6.6 ± 0.2 mM for d-alanine. Several coenzymes were without effect when added to the reaction mixture. The participation of d-alanine oxidase in the oxidation of l-alanine was demonstrated. The evidence is based on (i) results of cellular fractionation; (ii) labeling experiments; (iii) inhibition studies with aminooxyacetate and cycloserine; (iv) denaturation experiments; and (v) demonstration of the presence of an active racemase.